THE INFLUENCE OF PRICE, PRODUCT INFORMATION, AND ONLINE CONSUMER REVIEWS ON PURCHASE DECISIONS: THE MODERATING ROLE OF HALAL - Naila Rahmatul Jannah; Ubaidullah Muayyad (STAI Nusantara Kota Banda Aceh, 2026)
This research is designed regarding the impact of price, product information, as well as online customer reviews influence buying choices, involving halal awareness serving as a moderating factor. A quantitative method was employed utilized, focusing on Tokopedia users in Kabupaten Sumenep as the study population. The research involved approximately 152 respondents. The data were examined by applying the Partial Least Squares (PLS) technique method using SmartPLS software. The findings indicate indicating that price has a significant and positive influence on buying decisions (β = 0.336; t = 4.107; p = 0.000), product information also exerts a significant and positive effect (β = 0.382; t = 6.189; p = 0.000), as well as online customer reviews likewise demonstrate a significant and positive effect on purchasing decisions (β = 0.419; t = 7.545; p = 0.000). Furthermore, halal awareness was found to moderate the influence of price (β = 0.363; p = 0.000), product information (β = 0.161; p = 0.004), and online consumer reviews (β = 0.304; p = 0.000) on buying decisions, strengthening the relationship between the variables